Keanekaragaman dan Kelimpahan Predator pada Taman Maccini Sombala Makassar dan Ekosistem Persawahan Kiru-Kiru Kabupaten Barru - N Noerfitryani; Irma Hakim; Andi Rahayu Anwar; S Syamsia; M. Yahya (Fapetrik-UMPAR, 2021)
The existence of predatory insects is essential to know because they have contributed significantly to an ecosystem. This study aimed to determine the abundance and diversity of predators in Maccini Sombala Park, Makassar, and the paddy field in Kiru-Kiru Sub-District, Barru Regency, South Sulawesi. The selection of the two locations was carried out based on the ecosystem conditions in each place, Maccini Sombala Park is a city park in which there are various types of plants that are habitat for insects including predatory insects, as well as in the paddy field ecosystem in Kiru-Kiru Sub-District, based on the results of the observation in the field, in that ecosystem there were symptoms of pest attack such as stem borers and several other types of insects including insects predator on rice plant. This study was conducted by direct observations of purposive sampling and insects sampling using sweep net traps. The highest relative abundance value of natural enemies was found in the family Araneidae 37% in Maccini Sombala Park, and the lowest relative abundance of the family Coccinellidae was 2.3%. The highest relative abundance value of natural enemies in the paddy field of Kiru-Kiru Sub-District was found in the family Coccinellidae 54.3%, and the lowest relative abundance of the family Formicidae was 2.5%. The diversity index values of predators in both places as moderate diversity category, and the evenness index values of the two ecosystems showed that high evenness.